Analysis on the Value Implication and Implementable Path of Legal Education in Colleges and Universities in the View of Multimedia - Jiang Li (Advances in Multimedia)
Legal education is an indispensable part of talent training in colleges. Under the current background of the times, training talents who understand, know, and abide by the law is an indispensable mission of colleges. The development of multimedia will have many impacts on the legal education. Considering the legal education from the perspective of multimedia is the basic requirement to comply with the reform of teaching mode in colleges. This paper summarizes the research on the value, research status, and effectiveness of the legal education and then analyzes the value implication of strengthening the legal education in the perspective of multimedia and analyzes the specific problems it faces. The legal education is essentially a dynamic communication process. In the process of dynamic communication, the value of content, the efficiency of dissemination, the matching of supply and demand, and the initiative of feedback need to be taken into account. This paper analyzes these indicators through the hierarchical analysis method and finally puts forward the practical path of legal education under the multimedia vision, in order to provide guidance for the current work of legal education.